Education and assertive communication training for passive smoking prevention: A community intervention in Sarroanging Hamlet, Jeneponto District - Karini, Tri Addya; Putri, Asnita; Munawirah, Nur; Amalia, Salwa (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2025)
Despite growing awareness of the harms of secondhand smoke, rural communities often lack targeted interventions that empower passive smokers through education and communication training. Previous studies have primarily focused on tobacco control from the smoker's perspective, with limited integration of assertive communication as a preventive tool. This study aimed to assess the effectiveness of educational outreach combined with assertive communication training in increasing knowledge and behavioral skills among residents exposed to secondhand smoke in Sarroanging Hamlet, Jeneponto District. Employing both quantitative and qualitative methods, the intervention included psychoeducation sessions on the dangers of passive smoking and structured assertive communication role plays. Data were collected using pretest and posttest questionnaires alongside observational assessments. Findings revealed a significant increase in knowledge scores from 65.67 to 81.00 post-intervention. Additionally, there was notable improvement in assertive behavior, as participants demonstrated enhanced ability to express objections, reject invitations to tolerate indoor smoking, and issue warnings to active smokers. Role-playing exercises effectively reinforced these behaviors. This community-based approach highlights the value of combining educational and behavioral strategies to reduce secondhand smoke exposure, offering a replicable model for rural public health interventions.